Recent trends in seroprevalence of rubella in Korean women of childbearing age: a cross-sectional study - Rihwa Choi; Yejin Oh; Youngju Oh; Sung Ho Kim; Sang Gon Lee; Eun Hee Lee (BMJ Open)
Objectives The aim of this study was to investigate the immunity against rubella using the serological status of rubella-specific IgG antibodies (antirubella IgG) in Korean women of childbearing age (15–49 years).Design Retrospective cross-sectional study.Setting Population-based cross-sectional study in South Korea.Participants Between January 2010 and December 2017, test results from Korean women aged 15–49 years who had visited an obstetric private clinic (nationwide institutions) and had requested rubella-specific IgG antibody tests from Green Cross Laboratories were obtained from the laboratory information system.Results Between 2010 and 2017, antirubella IgG test results from 328 426 Korean women aged 15–49 years who had visited private obstetric clinics (1438 institutions nationwide) were retrospectively analysed by tested year, age, cohort and geographic regions. Over the 8-year study period, the rate of unimmunised women ranged from 7.8% to 9.7%. Multivariable-adjusted logistic regression models showed that the odds of being immune to rubella (positive and equivocal results of antirubella IgG test) were lower in 2017 compared with 2010, in women in their 40s, in a pre-catch-up cohort and in women living in Incheon, Busan, South Gyeongsang, North and South Jeolla and Jeju provinces (p<0.0001).Conclusions In consideration of the factors associated with prevalence of women unimmunised to rubella, future public health efforts should be focused on catch-up activities. The results of this study could be used to strengthen disease control and prevent rubella, including a nationwide immunisation programme.